2005
DOI: 10.1007/s11055-005-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

Glial Fibrillary Acidic Protein in Astrocytes in the Human Neocortex

Abstract: Glial fibrillary acidic protein (GFAP), expressed in the brain by astrocytes, is one of the major immunocytochemical markers of these cells. The aim of the present work was to study the structure of GFAP-positive astrocytes in the human neocortex. Immunocytochemical confocal laser microscopy was used to characterize the main types of GFAP-immunoreactive astrocytes in the human neocortex. These were astrocytes of layer I, forming the superficial glial delimiting membrane, along with transmembrane astrocytes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…These cells appear to have two types of processes: tangential fibres travelling radially; and ‘cable-like’, long, vertical astroglial processes (Colombo and Reisin 2004). Further characterisation of the latter by Colombo and colleagues showed millimetre-long, tortuous and varicosity-free interlaminar projections (Korzhevskii et al 2005; Oberheim et al 2009) originating from the somata located in the neuronal cell body-free layer I, and terminating in layer III or IV cortical neuropil in large buttons. Electron microscopy studies revealed that these endings possessed a multilamellar structure and mitochondria (Colombo et al 1997).…”
Section: Complex Structure and Morphology Of Human Astrogliamentioning
confidence: 99%
“…These cells appear to have two types of processes: tangential fibres travelling radially; and ‘cable-like’, long, vertical astroglial processes (Colombo and Reisin 2004). Further characterisation of the latter by Colombo and colleagues showed millimetre-long, tortuous and varicosity-free interlaminar projections (Korzhevskii et al 2005; Oberheim et al 2009) originating from the somata located in the neuronal cell body-free layer I, and terminating in layer III or IV cortical neuropil in large buttons. Electron microscopy studies revealed that these endings possessed a multilamellar structure and mitochondria (Colombo et al 1997).…”
Section: Complex Structure and Morphology Of Human Astrogliamentioning
confidence: 99%
“…Human U-87 glioblastoma/astrocytoma cells were used as a model system for this study and were confirmed to have an astrocyte phenotype by using the astrocyte marker GFAP (data not shown; Korzhevskii et al, 2005). U-87 glioblastoma/astrocytoma cellular morphology was captured by differential interference contrast (DIC) microscopy ( Fig.…”
Section: Gwbs Are Present In the Cell Body And Cytoplasmic Projectionmentioning
confidence: 99%
“…Thus, GFAP serves as a biomarker of astrogliosis, and serum levels have been found to be highly correlated with astrocytoma volume (Brommeland, Rosengran, Fridland, Hennig, & Isaksen, 2007). Local levels of GFAP, along with elevated cytokines have been implicated as driving factors in astrocytic differentiation and growth, angiogenesis and astrogliosis, and may alter the tumor microenvironment so that immune cells do not attack the tumor cells (Korzhevskii, Otellin, & Grigor’ev, 2005; Radeff Huang, Seasholtz, & Brown, 2005; Schneider, Sailer, Ansorge, Firsching, & Reinhold, 2006). Altered GFAP levels have also been described in post-mortem samples of brain tissue from physically healthy individuals with major depressive disorder (Davis et al, 2002; Muguel-Hidalso, 2000).…”
Section: Discussionmentioning
confidence: 99%